Eksistensi UNCLOS 1982 dalam Upaya Penegakan Hukum Laut Internasional di Perairan Negara Pantai - Yulia Wiliawati; Danial Danial; Fatkhul Muin (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
The United Nations Convention on the Law of the Sea 1982 (UNCLOS 82) is an international treaty resulting from the United Nations Conference on the Law of the Sea. The Law of the Sea Convention defines the rights and responsibilities of states in the use of the world's oceans and establishes guidelines for business, the environment, and the management of marine natural resources. The problems are: First, how is the existence of UNCLOS 82 in the efforts to enforce international maritime law in Indonesian waters? Second, how is the implementation of UNCLOS 82 on the Indonesia vs Tiongkok conflict in Natuna? The method used is normative juridical, with an approach to legal principles. while the data analysis is a qualitative juridical analysis, namely analyzing the identification of problems based on secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. The results of this study are: First, the existence of UNCLOS 82 in efforts to enforce international maritime law in Indonesian waters is regulated in Article 37 (1) UNCLOS 82. Based on the provisions of Article 73 (1) of UNCLOS 1982, the coastal state in exercising its sovereign rights can board ships, examine, arrest and carry out judicial proceedings, as necessary to ensure compliance with the laws and regulations established by him in accordance with the provisions of the Convention. Furthermore, Article 73 paragraph (2) of Unclos 1982. The coastal state may be subject to court proceedings, as necessary to ensure compliance with the laws and regulations it has established in accordance with the provisions of this Convention. Second, the implementation of UNCLOS 82 in Natuna includes first, improving the capture fisheries licensing system and mechanism. The number of fishing vessels allowed to operate in a fishing area does not exceed the number of catches allowed (80% MSY) so that the capture fisheries business can take place profitably and sustainably.